Music composer and professor: a comparative view - Barreiro, Aguida C. M.; Barreiro, Daniel Luís (Comunicação & Educação, 2001)
This article makes a comparative analysis of the music composer and of the professor's work using a reflexive approach. Both are creative professionals, who are responsible for building communicative and educative capabilities, among other things. The authors defend music education that develops the student's capacity to explore the unknown, to question and to dare to develop individual answers. Likewise, they also defend an educational posture in which teaching and learning are constructive processes in one's search for autonomy. Points in common in both of their practices of process construction bring up the interest in the exchange of ideas between these fields of knowledge.